Roma/Ciganos and the Condition of Internal Strange in Portuguese Society: The Construction of Otherness - Maria Manuela Mendes; Magano, O. (Simmel and Beyond The Contemporary Relevance of Simmel’s Thought, 2022)
In Portugal, the Roma/Ciganos have been subjected to state measures engendering repression, expulsion, punishment and conviction dating back to 1526. Since their arrival in Europe, they have always been treated with suspicion and targeted rejection. Even today in Portugal and other European countries, anti-gypsyism is a well-established phenomenon in institutions and daily life. They are the eternal and “internal strangers”, despite having no other homeland of reference. Simmel addresses the tense relation not only of repulsion, distance, but also of approximation between the stranger and the non-stranger, a situation that contains important dualisms to be unveiled, such as identity versus alterity and distance versus closeness. In fact, there is a tendency to emphasise the general qualities we have in common with the stranger in Simmel and to accentuate the particularities, but we can also deny the factors of similarity, as is often the case with Ciganos. Generally, they are perceived in an essentialist and stigmatizing way, as a homogeneous and monolithic group. The literature about them oscillates between their exoticization, curiosity, romanticization and dangerousness. Data derived from case studies carried out by the authors is used to explain how Ciganos embody this metaphorical figure and as such indicate an ongoing relationship of strangeness and tension that marks the history of the interaction between the majority and the Ciganos.